Influence of Th1/Th2 cytokines and nitric oxide in murine systemic infection induced by Sporothrix schenckii - Maia, DCG; Sassa, M. F.; Placeres, MCP; Carlos, Iracilda Zeppone [UNESP] (Springer, 2006)
In an attempt to elucidate the effects of Sporothrix schenckii infection on the immune response, our laboratory has developed a murine model of disseminated sporotrichosis. Helper T cells can be further subdivided into Th1 and Th2 phenotypes. The differentiation of two subsets of T lymphocytes is driven by IL-12 and IL-4 cytokines, respectively. Th1 cells produce IFN-gamma that activate macrophages and promote cell-mediated immunity. In addition, we found low levels of iNOS and NO production in the initial (1st and 2nd weeks) and final (9th and 10th weeks) periods of the infection, in contrast with the period of week 4 to 7 of elevated values. The determination of IFN-gamma and IL-12 are in agreement with NO/iNOS detection, showing the presence of cellular immune response throughout the infectious process. However, the production of IL-4 shows an increase in levels after the 5th and 6th weeks suggesting a participation of Th2 response in this period as well. Regarding these results, the study demonstrated that in experimental sporotrichosis infection the cellular immune response participated throughout the period analyzed as a nitric oxide dependent mechanism. In contrast, the presence of Th2 response began in the 5th week, suggesting the participation of humoral immune response in advanced stages of sporotrichosis.
Keywords: cellular and humoral responses; cytokines; iNOS; nitric oxide; Sporothrix schenckii